2015
DOI: 10.1021/nl5041572
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Frequency Metasurfaces for Broadband Anomalous Reflection and High-Efficiency Spectrum Splitting

Abstract: Ultrathin metasurfaces have recently emerged as promising materials that have huge potential to enable novel, flat optical components, and surface-confined, miniature photonic devices. Metasurfaces offer new degrees of freedom in molding the optical wavefronts by introducing abrupt and drastic changes in the amplitude, phase, and/or polarization of electromagnetic radiation at the wavelength scale. By carefully arranging multiple subwavelength anisotropic or gradient optical resonators, metasurfaces have been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
209
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(219 citation statements)
references
References 39 publications
8
209
1
1
Order By: Relevance
“…Recently, metasurfaces in metal/insulator/metal (MIM) configuration have been widely used in photonic research [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Such structures typically consist of a layer of planar metallic resonators and a continuous metallic film separated by a dielectric spacer (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, metasurfaces in metal/insulator/metal (MIM) configuration have been widely used in photonic research [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Such structures typically consist of a layer of planar metallic resonators and a continuous metallic film separated by a dielectric spacer (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)). Based on MIM metasurfaces, a variety of wave-manipulation effects have been realized in a wide frequency range, including perfect absorption [2][3][4][5], polarization control [6][7][8], phase modulation [9][10][11], anomalous light reflection [12][13][14], flat-lens focusing [15,16], and holograms [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [82] Li et al suggested a simple design to realise a broadband perfect reflector across the visible frequency range by using a single gradient meta-atom design. Rather than several discrete sized elements in the unit cell [83,84], this design is basically an array of trapezoid shaped Ag nanorods coupled with an optically thick Ag film separated by a SiO 2 spacer [5,85].…”
Section: Metal Antenna Arraymentioning
confidence: 99%
“…Because the thickness of the antenna is of deep-subwavelength scale the light propagation path can be neglected and the phase discontinuity is only induced by the ultrathin metasurface. This produces a reflection of the beam to an arbitrary direction determined by the gradient of the phase change, and since in the configuration described in [82] there is no spatial-variant phase shift in the -direction, generalised Snell's law for reflection [83] is reduced to…”
Section: Metal Antenna Arraymentioning
confidence: 99%